Solve for y cube root of y=-9

Math
y3=-9
To remove the radical on the left side of the equation, cube both sides of the equation.
y33=(-9)3
Simplify each side of the equation.
Tap for more steps…
Multiply the exponents in (y13)3.
Tap for more steps…
Apply the power rule and multiply exponents, (am)n=amn.
y13⋅3=(-9)3
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
y13⋅3=(-9)3
Rewrite the expression.
y1=(-9)3
y1=(-9)3
y1=(-9)3
Simplify.
y=(-9)3
Raise -9 to the power of 3.
y=-729
y=-729
Solve for y cube root of y=-9

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top